2018
DOI: 10.3233/wor-182687
|View full text |Cite
|
Sign up to set email alerts
|

Are core self-evaluations a suitable moderator in stressor-detachment relationships? A study among managers’ perceived job demands, detachment and strain reactions

Abstract: The authors tested whether CSE was able to moderate the relationship between job demands, psychological detachment and different stress reactions. Although we found a significant interaction effect, CSE may be too distal to moderate all respective associations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…The findings of our second study seem therefore in line with prior studies that have shown that detachment has a stronger relationship with exhaustion than disengagement (Sonnentag & Fritz, 2007), and that personality factors show a strong connection to burnout dimensions (Swider & Zimmerman, 2010). Given that prior studies have either investigated the role of CSE with single (Hentrich et al, 2018) or aggregated scores of different burnout dimensions (Best et al, 2005), our findings extend these prior findings by separating the effect of CSE (and detachment) for two aspects of burnout. Furthermore, as prior research has mainly focused on identifying factors that hinder psychological detachment (Sonnentag & Fritz, 2015), our results add to the existing literature on positive resources at work.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…The findings of our second study seem therefore in line with prior studies that have shown that detachment has a stronger relationship with exhaustion than disengagement (Sonnentag & Fritz, 2007), and that personality factors show a strong connection to burnout dimensions (Swider & Zimmerman, 2010). Given that prior studies have either investigated the role of CSE with single (Hentrich et al, 2018) or aggregated scores of different burnout dimensions (Best et al, 2005), our findings extend these prior findings by separating the effect of CSE (and detachment) for two aspects of burnout. Furthermore, as prior research has mainly focused on identifying factors that hinder psychological detachment (Sonnentag & Fritz, 2015), our results add to the existing literature on positive resources at work.…”
Section: Discussionsupporting
confidence: 90%
“…In line with this finding, we expected CSE also to support the effect of psychological detachment for lowering feelings of burnout. However, with regard to the exhaustion component, Hentrich et al (2018) were not able to support such an expected moderation effect of CSE with detachment in their study.…”
Section: Health Impairment Processmentioning
confidence: 60%
See 3 more Smart Citations